Rifampicin induced thrombocytopenia in daily antituberculous regimen treatment - Mechan, Victor (2010)
We present the case of a 31 year-old patient with the diagnosis of lung tuberculosis by lung X-ray and positive acid alcohol resistant bacillus in sputum, who after 10 days of oral treatment with isoniazid, ethambutol, pyrazinamide and rifampicin (RFP), developed severe hemorrhagic manifestations associated with severe thrombocytopenia (2 000/mL) and slight right body hemiparesis. There was complete normalization of platelet count and motor function five days after suspension of the four drugs. We decided to re-expose the patient sequentially to the four drugs and after 12 hours of receiving RFP again developed severe thrombocytopenia (2 000/mL) not occurring with the other three drugs, and normalized completely after 36 hours of drug suspension. Later on, the addition of parenteral streptomycin successfully completed the treatment. The current case demonstrates a not very frequent adverse effect of a first line drug for the treatment of tuberculosis, which should be considered as a very serious complication and whose management should include the immediate and indefinite suspension of the drug in the affected patient, because of the high likelihood of having the same response every time he is challenged during his life.